Restructuring of consultative-diagnostic centers on principles of public-private partnership - Kravchenko, V. V. (Journal of Education, Health and Sport, 2018)
The aim of the study is to substantiate the conceptual approaches to the restructuring of the Consultative and Diagnostic Centers (CDCs) - as a purposeful change in their structure, management system, operating activities on the principles of public-private partnership (PPP). Materials and methods. To achieve this aim, general scientific methods of analysis, synthesis, generalization, interpretation of scientific data, as well as systematic approach, dialectical principles of comparison were used in the work. Results. Based on a comprehensive study of the state of the organization and the activities of the existing CDC system, it is established that for its optimization it is necessary to implement PPP mechanisms and restructuring the system. It is shown that the development of CDC depends on the level of funding, quality of management, planning process, organization of production and implementation of public-private partnership mechanisms. Conceptual directions and priority principles of restructuring of the CDC system are grounded. Conclusions. As a result of the study, it was concluded that to ensure the development of a system of consultative and diagnostic centers, their structure, functions, organization, and management should be brought into line with the requirements of PPP. It is possible to achieve this by implementing the conceptual directions of restructuring of the CDC system proposed in the article.